Analisis Customer Journey Lawson: Strategi Visual Merchandising dan Store Layout di Lawson Stasiun Manggarai - Kurniaty Kurniaty; Andi Muhammad Sadat (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to analyze the impact of visual merchandising strategies and store layout at Lawson, Manggarai Station, on customer experience across the five stages of the customer journey: Awareness, Interest, Decision, Retention, and Advocacy. Using a qualitative method with in-depth interviews involving 10 respondents, the research highlights the significant role of visual elements such as window displays, efficient product layouts, and promotional signage in attracting attention and fostering customer loyalty. The findings indicate that strategic location, attractive promotions, and loyalty programs effectively drive customer retention and advocacy. Recommendations include developing social media strategies, improving store layouts, and optimizing loyalty programs to enhance modern shopping experiences.